Melanosis Coli - An Atypical Presentation - Ahasan, HAM Nazmul; Khan, Mohammad Ashik Imran; Mahbub, Md Shahriar; Alam, Md Billal; Miah, Md Titu; Gupta, Ratan Das; Arif, Khan Mohammad (Journal of Medicine, 2010)
Melanosis Coli is described as black or brown discoloration of the mucosa of the colon. It is a benign condition, which arises from anthraquinone laxative abuse and usually has no symptoms of its own. Though not a very rare condition, to the best of our knowledge, no case has been reported on melanosis coli in Bangladesh . Here we report a case of middle aged lady presenting with passage of blood mixed stool for one year. Colonoscopy was performed which revealed melanosis coli and which was later confirmed by histopathology. Not thought to be a pre malignant condition, it has been found in some patients with other diseases. Keywords: Melanosis coli; Anthraquinone; Lipofuscin; Laxative; Bangladesh DOI: 10.3329/jom.v11i2.5469 J MEDICINE 2010; 11 : 183-185